2014
DOI: 10.4028/www.scientific.net/amr.889-890.1284
|View full text |Cite
|
Sign up to set email alerts
|

Design of Notification System Illegal Parking Vehicles on Campus

Abstract: The increase in the number of private cars as well as non-standard parked behavior has brought great pressure to campus traffic. In order to control this non-standard parked behavior, orderly and reasonable guide and regulate owners to develop good parking habits, we design a vehicle parking violation notification system. A system is designed in the article to record illegal parking information of vehicles. A working principle of this system is that a wireless MMS image terminal captures image information of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus far, a few studies on illegal parking have been reported, such as [1][2][3][4]. However, only the related technol-ogy framework has been constructed and there is still a lack of a systemic, concrete analysis and an understanding of the image processing algorithm for illegal parking detection and recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, a few studies on illegal parking have been reported, such as [1][2][3][4]. However, only the related technol-ogy framework has been constructed and there is still a lack of a systemic, concrete analysis and an understanding of the image processing algorithm for illegal parking detection and recognition.…”
Section: Introductionmentioning
confidence: 99%